Nursery Management Information System:An Efficient Tool for Nursery Management - Ratha Krishnan, P.; Dudawat, Kirtesh (Indian Forester, 2016)
Plant nursery record management is generally through note books, which is laborious and consume more time for data entry and retrieval. To conquer this difficulty and attract youth towards nursery entrepreneurship, this unique Nursery Management Information System (NMIS) has been developed. It is developed using Java-SE, Swings at frontend and MySQL Workbench at backend. Along with it, Type-4 JDBC connectivity makes the software platform independent and increases its usability. NMIS database has been designed with modification, updation and revision facilities. NMIS is used for storing, handling and managing data related to nursery by maintaining seedling stocks, dispatch details, and handling communication between employees and administration. Access of data through various searches such as species-wise, date-wise search etc and facilities such as printing of bill facilitates easy data retrieval in desired mode. NMIS facilitates efficient nursery management while executing task in speedy and eco-friendly manner.